The far right in Western and Eastern Europe - Cheles, Luciano; Ferguson, Ronnie; Vaughan, Michalina (Harlow : Longman, 1995)
Bibliotheek François Vercammen
Engels
Monografie
Keywords: extreemrechts; West-Europa.; Oost-Europa.